Composite electrolyte and preparation method and application thereof

By adding specific additives to the electrolyte of lithium-ion batteries and optimizing their formulation and proportion, the problem of lithium-ion batteries being easily thermally runaway at high temperatures is solved, and the thermal safety performance and cycle life of the battery are significantly improved.

CN119650852APending Publication Date: 2025-03-18ENKE TIANRUN NEW ENERGY MATERIALS (SHANDONG) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411821803.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The electrolyte of existing lithium-ion batteries is prone to thermal runaway at high temperatures, leading to high risk of fire and explosion accidents, and flame retardant additives are unfavorable to the stability of solid electrolyte membranes.

Method used

A composite electrolyte was designed. By adding methyl trimethoxysilane, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether and triethylene glycol monomethyl ether as additives to the electrolyte, its formulation and addition ratio were optimized to improve the thermal safety performance of the battery.

Benefits of technology

The composite electrolyte can effectively reduce the flammability of traditional organic electrolytes, inhibit or avoid the combustion of lithium-ion batteries, and improve the thermal stability and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650852A_ABST
    Figure CN119650852A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to a composite electrolyte and a preparation method and application thereof, the composite electrolyte comprises an organic solvent, an electrolyte lithium salt and an additive; and the additive comprises methyl trimethoxy silane, 1, 1, 2, 2-tetrafluoroethyl-2, 2, 2-trifluoroethyl ether and triethylene glycol monomethyl ether. By optimizing the formula and the adding proportion of the composite electrolyte additive, the thermal safety performance of the battery can be improved, the safety problem caused by thermal runaway is reduced, the flammability of the traditional organic electrolyte is reduced, and the combustion of the rechargeable battery is inhibited or avoided. In a charge-discharge test, the battery added with the composite flame retardant slightly improves the charge storage capacity of the battery at high temperature, and the specific capacity of the battery is improved; according to the present invention, under the variable magnification charge-discharge condition, the high specific capacity can be maintained, the rapid charge-discharge can be performed under the large current condition, the low energy consumption and the low heat generation can be maintained, and the strong high temperature stability can be provided;
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a composite electrolyte and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles, and other fields due to their high energy density, environmental friendliness, and long cycle life. However, fires and explosions caused by lithium-ion batteries still occur frequently, and the safety performance of lithium-ion batteries still needs to be further improved. The electrolyte of lithium-ion batteries is one of the key materials that determines their cycle stability, high-voltage stability, and safety.

[0003] Common lithium-ion electrolytes are primarily composed of flammable organic solvents with low flash points (such as ethyl carbonate (EC), propylene carbonate (PC), ethyl carbonate (EMC), diethyl carbonate (DMC), and diethyl carbonate (DEC)) and thermally unstable lithium salts (such as LiPF6). Therefore, when the internal temperature of the battery rises due to abuse or shock, the organic solvents can easily decompose, further increasing the temperature and ultimately leading to thermal runaway.

[0004] Introducing flame-retardant additives into the electrolyte is one of the most cost-effective methods. It can prevent internal reactions when the battery temperature rises, effectively reducing the risk of thermal runaway. Existing flame-retardant additives such as methyltrimethoxysilane can improve the thermal stability of the electrolyte, but they are not conducive to the stable formation of the solid electrolyte interface (SEI). Summary of the Invention

[0005] The purpose of the present invention is to provide a composite electrolyte and its preparation method and application, so as to overcome the shortcomings of the existing technology. The composite electrolyte additive designed by the present invention can improve the thermal safety performance of the battery, reduce the safety problems caused by thermal runaway, reduce the flammability of traditional organic electrolytes, and inhibit or avoid the combustion of rechargeable batteries.

[0006] In order to achieve the above object, the technical solution of the present invention is:

[0007] In a first aspect, the present invention provides a composite electrolyte comprising an organic solvent, an electrolyte lithium salt and an additive; the additive comprises methyltrimethoxysilane, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether and triethylene glycol monomethyl ether.

[0008] In some other embodiments, the concentration of the electrolyte lithium salt in the organic solvent is 0.5-2 mol / L; the volume of the additive in the organic solvent is 1-10%; this concentration ratio can ensure the flame retardant effect while minimizing the impact of the side effects of the flame retardant on the electrochemical properties of the electrolyte.

[0009] Preferably, the concentration of the electrolyte lithium salt in the organic solvent is 1 mol / L; and the volume of the additive in the organic solvent is 5%.

[0010] In some other embodiments, the volume ratio of methyltrimethoxysilane, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether and triethylene glycol monomethyl ether is (1-3): (1-3): 1;

[0011] Preferably, the volume ratio of methyltrimethoxysilane, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether and triethylene glycol monomethyl ether is 1:1:1.

[0012] In some other embodiments, the organic solvent includes ethylene carbonate, diethyl carbonate, and ethyl methyl carbonate;

[0013] The volume ratio of ethylene carbonate, diethyl carbonate and ethyl methyl carbonate is (1-3): (1-3): 1;

[0014] Preferably, the volume ratio of ethylene carbonate, diethyl carbonate and ethyl methyl carbonate is 1:1:1.

[0015] In some other embodiments, the electrolyte lithium salt is one or more of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, or lithium hexafluorophosphate;

[0016] Preferably, the electrolyte lithium salt is lithium hexafluorophosphate.

[0017] In a second aspect, the present invention provides a method for preparing the composite electrolyte described in the first aspect, which is obtained by mixing an organic solvent, an electrolyte lithium salt and an additive.

[0018] In some other embodiments, the mixing conditions are: room temperature and in an inert atmosphere.

[0019] In a third aspect, the present invention provides use of the composite electrolyte described in the first aspect in a lithium-ion battery.

[0020] In a fourth aspect, the present invention provides a lithium-ion battery comprising a positive electrode, a negative electrode, a separator and the composite electrolyte described in the first aspect.

[0021] In some other embodiments, the lithium-ion battery is a ternary positive electrode material lithium-ion battery, a lithium iron phosphate positive electrode material lithium-ion battery, a lithium manganese iron phosphate positive electrode material lithium-ion battery, a lithium nickel manganese oxide positive electrode material lithium-ion battery, and a high nickel positive electrode material lithium-ion battery.

[0022] Beneficial effects of the present invention:

[0023] (1) By optimizing the formula and addition ratio of the composite electrolyte additive, the present invention can improve the thermal safety performance of the battery, reduce the safety problems caused by thermal runaway, reduce the flammability of traditional organic electrolytes, and inhibit or avoid the combustion of rechargeable batteries.

[0024] (2) The composite electrolyte additive in the present invention is composed of MTMS, hydrofluoroether 347 and TEM; wherein, MTMS is a silane compound, and its unique chemical structure makes it improve the thermal stability and flame retardant properties of the material, but the SEI film it generates is not stable enough and is easy to decompose. Hydrofluoroether 347 has excellent chemical and thermal stability, is non-flammable, and is often used as an environmentally friendly solvent. Due to the strong electronegativity and weak polarity of its fluorine atoms, it can improve the compatibility of the electrode / electrolyte interface and form a dense and stable LiF-rich SEI, which is beneficial to improve the shortcomings of MTMS and improve the coulombic efficiency of the battery during the cycle; TEM has the chemical properties of alcohol and ether, has a high flash point, can dissolve a variety of organic solvents, can optimize the negative electrode SEI film, and improve the compatibility between the electrolyte and the negative electrode. The passivation layer composed of its reduction product has strong polarity, good adhesion to the negative electrode, and is not easy to fall off. In addition, its excellent spatial structure is conducive to Li + Hydrofluoroether 347 and TEM were added to optimize MTMS to achieve better flame retardant effect.

[0025] (3) The battery to which the composite flame retardant additive is added in the present invention shows higher charge and discharge stability and longer cycle life in the 1C long cycle performance test. After 100 cycles at 40°C, the additive can slow down the aging rate of the battery during repeated charge and discharge at high temperature and maintain the specific capacity of the battery. In the charge and discharge test, the battery to which the composite flame retardant is added slightly improves the battery's ability to store charge at high temperature and improves the specific capacity of the battery; under variable rate charge and discharge conditions, it can maintain a high specific capacity, can quickly charge and discharge under high current conditions, while maintaining low energy consumption and heat generation, and has stronger high temperature stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The accompanying drawings, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0027] Figure 1 This is a picture showing the combustion time of different electrolytes after ignition in an embodiment of the present invention;

[0028] Figure 2 This is a cycling performance test of the battery at 1C current density at 40°C in an embodiment of the present invention, where A is an electrolyte with a flame retardant added and B is an electrolyte without a flame retardant added;

[0029] Figure 3 : This is the charge and discharge curve of the battery at 0.1C current density at 40°C in an embodiment of the present invention, where A is the electrolyte with added flame retardant and B is the electrolyte without added flame retardant;

[0030] Figure 4 The charge and discharge curves of the electrolyte with flame retardant added at different current densities at 40°C in the embodiment of the present invention are as follows;

[0031] Figure 5 The cycling performance at different current densities at 40°C in the embodiment of the present invention, where A is the electrolyte with added flame retardant and B is the electrolyte without added flame retardant;

[0032] Figure 6 This is the electrochemical impedance spectroscopy test in the embodiment of the present invention, where A is the electrolyte with added flame retardant, and B is the electrolyte without added flame retardant. DETAILED DESCRIPTION

[0033] Example 1

[0034] Step 1. Coating and production of electrode

[0035] Weigh 4 g of polyvinylidene fluoride (PVDF) powder, add 96 g of N-methylpyrrolidone (NMP), and stir on a magnetic stirrer until the powder is completely dissolved to make a 10% PVDF binder. Weigh 2.5 g of carboxymethyl cellulose (CMC) powder and 2.5 g of styrene-butadiene rubber (SBR), add 95 g of deionized water, and stir on a magnetic stirrer until the powder is completely dissolved to make a 2.5% CS binder.

[0036] First, weigh the LiFePO4 active material, Super-P, and CS binder in a mass ratio of 8:1:1, add them separately into the small box of the blender and stir to obtain a uniformly mixed slurry. Apply the slurry on aluminum foil with a 150um applicator, and then place the electrode in an 80°C forced air drying oven to dry. After the electrode is completely dry, slice it into circular electrode sheets with a diameter of 14 mm. After weighing, put it in the glove box for use. The surface density of the positive electrode sheet is 7-8 mg / cm -2 .

[0037] Weigh the graphite negative electrode material, Super-P, and CS binder in a mass ratio of 9:1:1, add them into the small box of the paddle mixer and stir to obtain a uniformly mixed slurry. Apply the slurry on the copper sheet with a 100um applicator, and then place the electrode in an 80°C forced air drying oven to dry. After the electrode is completely dry, slice it into circular electrode sheets with a diameter of 14 mm. After weighing, put it in the glove box for use. The surface density of the negative electrode sheet is 3-4 mg / cm -2 .

[0038] Step 2. Preparation of electrolyte

[0039] The solvents EMC:DMC:EC were mixed in a 1:1:1 volume ratio. The appropriate amount of LiPF6 was added to a concentration of 1 mol / L. The mixture was shaken at room temperature until the LiPF6 was completely dissolved. Methyltrimethoxysilane (MTMS), 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether (Hydrofluoroether 347), and triethylene glycol monomethyl ether (TEM) were then added in a 1:1:1 ratio of 5% by volume. LiPF6 was added as needed to maintain a lithium salt concentration of 1 mol / L. The mixture was shaken until fully dissolved. The mixture was sealed and used for further analysis. All operations were performed in an argon-filled glove box. For ease of experimental analysis, the LiPF6-EMC:DMC:EC-MTMS-Hydrofluoroether 347-TEM electrolyte containing the flame retardant additive was labeled A, and the LiPF6-EMC:DMC:EC electrolyte without the flame retardant additive was labeled B.

[0040] The above preparation method was used to prepare the corresponding electrolytes according to the following ratios: only MTMS, MTMS and hydrofluoroether 347 (1:1), MTMS and TEM (1:1), and hydrofluoroether 347 and TEM (1:1).

[0041] Step 3. Making a button battery

[0042] A lithium-ion button cell battery consists of a positive electrode, a negative electrode, a separator, an electrolyte, and a stainless steel casing. First, the positive electrode sheet coated with active material is placed on a CR2025 positive electrode casing. After placing a PP separator, 100 μL of electrolyte is added. The negative electrode sheet is then added, followed by a gasket and spring, and the negative casing is closed. The battery is assembled using a press in a glove box. After the battery rests for 12 hours, electrochemical tests, including charge and discharge, are performed. All of these steps are performed in an argon-filled glove box.

[0043] Step 4. Performance testing

[0044] (1) Self-extinguishing test

[0045] The flame retardancy of the electrolyte is determined by measuring the self-extinguishing time after ignition. Place 200 μL of the electrolyte solution in the battery case, ignite it with a flame eye for 3 seconds, and observe and record the extinguishing time of the electrolyte. Repeat this three times. Figure 1 These are pictures of the combustion of electrolytes with different flame retardant additives at different times after ignition.

[0046] Figure 1The following are pictures of the electrolyte without any flame retardant additives burning at different times after ignition. The self-extinguishing time is 35 seconds. The following are pictures of the electrolyte with only MTMS flame retardant additive burning at different times after ignition. The self-extinguishing time is 31 seconds. The following are pictures of the electrolyte with MTMS and hydrofluoroether 347 (1:1) flame retardant additives burning at different times after ignition. The self-extinguishing time is 29 seconds. The following are pictures of the electrolyte with MTMS and TEM (1:1) flame retardant additives burning at different times after ignition. The self-extinguishing time is 27 seconds. The following are pictures of the electrolyte with hydrofluoroether 347 and TEM (1:1) flame retardant additives burning at different times after ignition. The self-extinguishing time is 30 seconds. The following are pictures of the electrolyte with MTMS, hydrofluoroether 347, and TEM (1:1:1) flame retardant additives burning at different times after ignition. The self-extinguishing time is 25 seconds. By comparison, it can be seen that the electrolyte with the addition of MTMS, hydrofluoroether 347, and TEM (1:1:1) flame retardant additives has the shortest self-extinguishing time and the best flame retardant performance.

[0047] During the research and development process, the inventors discovered that by reducing any one of the components of the above-mentioned additives or replacing the components of the electrolyte of the present application, the flame retardant effect of the electrolyte as a whole on the battery is significantly reduced; by adding other raw material components on the basis of the additives of the present application, the overall effect of the electrolyte is not significantly improved, and there are even cases where the overall effect of the electrolyte is reduced. Therefore, the raw material components in the electrolyte of the present application play a role in enhancing flame retardancy as a whole, and thus play a role in improving the overall safety of the lithium battery. The amount of each raw material in the additive of the present application is also very critical. During the experiment, the inventors adjusted the amount of some raw materials in the additives. It was found that the flame retardant effect of the composition after the adjustment of the amount on the electrolyte was significantly reduced.

[0048] (2) Long cycle performance test

[0049] The long cycle performance test conditions are: 40°C, 1C current density, and a test voltage range of 2.5 to 4.2V.

[0050] The cycling performance test results of the battery at 1C current density at 40°C are as follows: Figure 2 As shown in the figure, the assembled battery A with added composite flame retardant and the battery B without added flame retardant were tested for long cycle performance under 1C conditions. Figure 2As can be seen, Battery A, which added the composite flame retardant, achieved an average Coulombic efficiency of 98.5%, a maximum charge capacity of 197.9 mAh / g, a capacity of 168.7 mAh / g after 100 cycles, and a capacity retention rate of 85.2%. Battery B, which did not add the flame retardant, achieved a maximum charge capacity of 177.9 mAh / g, a capacity of 145.6 mAh / g after 100 cycles, and a capacity retention rate of 81.8%. It is clear that the addition of the composite flame retardant increased the charge-discharge capacity of the battery after 100 cycles, and the capacity retention rate also slightly improved.

[0051] (3) Constant current charge and discharge performance test

[0052] The constant current charge and discharge performance test conditions are: 40°C, 0.1C current density, and a test voltage range of 2.5 to 4.2V.

[0053] The charge and discharge performance test results of battery A with composite flame retardant added and battery B without flame retardant were carried out under 0.1C conditions. Figure 3 As shown, from Figure 3 It can be seen that the specific capacity of battery A can reach 245.9 mAh / g, and that of battery B can reach 241.8 mAh / g. It can be seen that the addition of the composite additive slightly improves the specific capacity of the battery at high temperature.

[0054] (4) Charge and discharge performance test at different rates

[0055] The conditions for the charge and discharge performance test at different rates are: 40°C, 0.2C, 1C, and 2C current densities, and a test voltage range of 2.5 to 4.2V.

[0056] Battery A with composite flame retardant was charged and discharged at 0.2C, 1C, and 2C at room temperature. Figure 4 As shown. Figure 4 It can be seen that when the charge and discharge rate is too fast, it is difficult for lithium ions to be inserted and removed in a short time, and the specific capacity decreases in the order of 0.2C, 1C, and 2C.

[0057] The battery A with composite flame retardant added and the battery B without flame retardant were tested for cycle performance at different rates at 40°C. Figure 5 As shown, from Figure 5It can be seen that Battery A, which added the composite flame retardant, has a higher specific capacity under variable rate conditions. For Battery A, the first charge capacity at 0.2C was 238.6 mAh / g. After variable rate cycling, the capacity at the fiftieth cycle at 0.2C was 228.6 mAh / g, with a capacity retention rate of 95.6%. Battery B, which did not add the flame retardant, showed a more rapid decrease in specific capacity, with a capacity retention rate of 73.8%. This indicates that the addition of the composite additive enhances the battery's variable rate performance and improves capacity retention to a certain extent.

[0058] (5) Electrochemical impedance spectroscopy

[0059] The conditions for electrochemical impedance spectroscopy are: at 25°C or 40°C, the test voltage range is 2.5 to 4.2 V, and the frequency is 0.01 to 10 5 Hz.

[0060] Electrochemical impedance spectroscopy was performed on battery A with composite flame retardant added and battery B without flame retardant to draw Nyquist diagrams. Figure 6 As shown, from Figure 6 It can be observed that at both 25°C and 40°C, the impedance of battery A with the composite flame retardant added is lower than that of battery B without the flame retardant. Moreover, at 40°C, the semicircle radius of the Nyquist plot of battery A with the composite flame retardant added is smaller than that at 25°C, while the semicircle radius of the Nyquist plot of battery B without the flame retardant remains essentially unchanged, indicating that the addition of the composite flame retardant can reduce the charge transfer resistance of lithium-ion batteries at 40°C.

[0061] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.

Claims

1. A composite electrolyte, characterized in that: The invention comprises an organic solvent, an electrolyte lithium salt and an additive; the additive comprises methyltrimethoxysilane, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether and triethylene glycol monomethyl ether.

2. The composite electrolyte according to claim 1, characterized in that The concentration of the electrolyte lithium salt in the organic solvent is 0.5-2 mol / L; the volume of the additive in the organic solvent is 1-10%; Preferably, the concentration of the electrolyte lithium salt in the organic solvent is 1 mol / L; and the volume of the additive in the organic solvent is 5%.

3. The composite electrolyte according to claim 1, characterized in that The volume ratio of methyltrimethoxysilane, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether and triethylene glycol monomethyl ether is (1-3): (1-3): 1; Preferably, the volume ratio of methyltrimethoxysilane, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether and triethylene glycol monomethyl ether is 1:1:

1.

4. The composite electrolyte according to claim 1, characterized in that: The organic solvent includes ethylene carbonate, diethyl carbonate and ethyl methyl carbonate; The volume ratio of ethylene carbonate, diethyl carbonate and ethyl methyl carbonate is (1-3): (1-3): 1; Preferably, the volume ratio of ethylene carbonate, diethyl carbonate and ethyl methyl carbonate is 1:1:

1.

5. The composite electrolyte according to claim 1, characterized in that: The electrolyte lithium salt is one or more of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, or lithium hexafluorophosphate; Preferably, the electrolyte lithium salt is lithium hexafluorophosphate.

6. A method for preparing the composite electrolyte according to any one of claims 1 to 5, characterized in that: The organic solvent, electrolyte lithium salt and additives are mixed to obtain the product.

7. The method for preparing a composite electrolyte according to claim 6, characterized in that: The mixing conditions are: room temperature and inert atmosphere.

8. Use of the composite electrolyte according to any one of claims 1 to 5 in a lithium ion battery.

9. A lithium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode, a separator and the composite electrolyte according to any one of claims 1 to 5.

10. The lithium ion battery according to claim 9, characterized in that: Lithium-ion batteries include ternary positive electrode material lithium-ion batteries, lithium iron phosphate positive electrode material lithium-ion batteries, lithium iron manganese phosphate positive electrode material lithium-ion batteries, lithium nickel manganese oxide positive electrode material lithium-ion batteries and high nickel positive electrode material lithium-ion batteries.